Estimation of serum malondialdehyde and assessment of DNA damage using comet assay in patients with oral submucous fibrosis. Issue 3 (29th April 2015) - Paulose, Swetha; Rangdhol, Vishwanath; Ramesh, Ramasamy; Jeelani, Siccandar Ali; Brooklyin, Sivakumar
Abstract: Aim: To quantify the level of serum malondialdehyde and extent of DNA damage using comet assay in patients with oral submucous fibrosis (SMF) in comparison to normal individuals and to correlate the extent of DNA damage with MDA levels. Methods: Study included 30 cases of SMF ( n = 30) and equal number of healthy volunteers. Serum malondialdehyde was measured using the thiobarbituric–trichloroacetitic acid (TBA–TCA) method. Comet assay was used to assess the DNA damage. Association between the extent of DNA damage and serum MDA levels was analyzed in SMF statistically. Results: Comet assay results showed that there was an increase in tail length, percentage of tail DNA and tail moment among SMF subjects ( P < 0.05). Serum MDA levels were elevated in SMF patients compared with healthy subjects. A significant positive correlation was observed between serum MDA levels and comet tail length in SMF group ( r = 0.56; P < 0.05). Conclusions: Patients with SMF have increased DNA damage and elevated levels of lipid peroxidation compared with healthy controls. Evaluation of MDA levels as an oxidative biomarker along with comet assay analysis will serve as a diagnostic tool to identify patients with high risk of malignant potential in SMF.